Treatment of obstruction of the superior vena cava by combination chemotherapy with and without irradiation in small-cell carcinoma of the bronchus. - Spiro, S G (1983)
In a randomised prospective trial of chemotherapy with and without radiotherapy in small-cell carcinoma of the bronchus, 37 of 366 patients presented with obstruction of the superior vena cava at the time of diagnosis. In the study all patients received four cycles of combination chemotherapy over a period of 12 weeks and, provided there was not progressive disease, then received either radiotherapy to the mediastinum and primary tumour followed by eight further courses of chemotherapy or eight cycles of chemotherapy alone. Of the 37 patients presenting with superior vena caval obstruction, nine had relapsed and treatment was stopped during or after the initial four cycles of chemotherapy. Of the remainder, 15 patients received radiotherapy plus chemotherapy and 13 chemotherapy alone. After four cycles of chemotherapy (12 weeks) 21 of the 37 patients had initial complete relief of symptoms secondary to superior vena caval obstruction, 10 had substantial but partial relief, and six had no relief. Twelve patients developed recurrence of superior vena caval obstruction, of whom six had received radiotherapy and four chemotherapy alone; two relapsed in the initial 12 weeks of the study. The median survival of the patients with superior vena caval obstruction allocated at diagnosis to either treatment arm was identical. The survival of patients with obstruction was similar to that of other patients in the main study. Chemotherapy is an effective treatment for superior vena caval obstruction and there appears to be no additional advantage in giving radiotherapy after 12 weeks of cyclical chemotherapy.